Quantum-mechanical prediction of the behavior of quantum trigger on a two-qubit cell of boron in silicene - Andrey N. Chibisov; Mary A. Chibisova (Modern Electronic Materials)
The problem of creating energy-efficient quantum computers capable of performing quantum operations without errors is a significant scientific challenge in modern nanoelectronics. This type of computer can be developed using quantum transistors that contain hole qubits and are capable of performing operations on them. Hole qubits are a promising technology for quantum computers due to their strong spin-orbit interaction and the ease of control with an electric field. In this work, the influence of spin dynamics of boron impurities on the electron charge transport and electrostatic potential in a silicene structure is theoretically investigated using the noncollinear spin density method. To study spin dynamics, we calculated the dependence of the total energy change of the atomic system on the angle of rotation of the spin magnetic moments on boron atoms. It was shown that the two-dimensional system B:Si behaves as a quantum switch, allowing operations on the local distribution of charge density and electrostatic potential, thereby processing quantum information. The obtained results will be important for the technology of designing and manufacturing two-dimensional energy-efficient quantum computer.